Analisis Penerapan Perencanaan Pajak (Tax Planning) PPH Pasal 21 sebagai Upaya Efesiensi Beban Pajak Wajib Pajak Badan - Dian Nur Febria; Suhirman Madjid (Majalah Sainstekes, 2019)
Tax is a deduction of corporate income, therefore the company needs a way that can be used to streamline the tax burden. One way that is used to make the tax burden is through tax planning. This study aims to find out the implementation of income tax planning article 21 and improve the efficiency of the company. This research is a descriptive analytical research that collected information and data, calculating and comparing income tax article 21 employee in accordance with Law Number 36, year 2008 about Income Tax, calculated and compared the amount of take home pay employee, and cost which is borne by the Company. This research data obtained from documentation at PT SKF Indonesia The Company also provides in-kind benefits as well as granting tax allowances to employees that will enlarge the company’s operating costs and in itself will reduce the tax payable. The application of income tax planning article 21 as a strategy for the efficiency of tax payments provided that if funds in Baitul Mall are insufficient. With the Tax Planning policy, it is not excessive in minimizing the tax burden so that it is not too miserly to issue assets in the form of income received by utilizing various possible loopholes that can be taken through tax regulations.